Hello all.

Is the following expression true?

[$\displaystyle ( p \equiv q ) \wedge ( r \equiv s ) $] $\displaystyle \Rightarrow$ [($\displaystyle p \wedge r ) \equiv ( q \wedge s )$]

If yes, please prove it.

Thanks

Printable View

- Sep 28th 2009, 07:21 AMResearcherA logic question
Hello all.

Is the following expression true?

[$\displaystyle ( p \equiv q ) \wedge ( r \equiv s ) $] $\displaystyle \Rightarrow$ [($\displaystyle p \wedge r ) \equiv ( q \wedge s )$]

If yes, please prove it.

Thanks - Sep 29th 2009, 07:56 AMGrandadProof by Truth Table
- Sep 29th 2009, 06:54 PMResearcher
Thank you Grandad.